Variations in atrial fibrillation ablation utilization and reimbursement among medicare beneficiaries: an observational study from 2013 to 2019. (3rd October 2022) - Fath, A; Abuasbeh, J; Abraham, B; Abusaleh, R; Olagunju, A; Aglan, A; Eldaly, A S; Mirza, G; Khurana, A
Abstract: Background: Atrial fibrillation (AF) pulmonary vein isolation ablation has been utilized increasingly yet variably in the USA. Purpose: To identify variations in AF ablation utilization and reimbursement among Medicare beneficiaries (MB). Methodology: We used a 100% sample of MB who underwent AF ablation from 2013 to 2019. We stratified data geographically (Northeast, South, West, and Midwest), identified the mean AF prevalence and the number of AF ablations per 100, 000 MB, and examined the correlation between AF prevalence and ablation. We also examined the number of cardiologists performing AF ablation per 100, 000 MB and the average number of AF ablation per individual cardiologist (ablation/cardiologist), as well as average submitted charge (ASC) for AF ablation. Additionally, we stratified data per urban versus rural areas as well as the gender of performing cardiologists and examined ablation/cardiologist and the ASC. Results: Geographic analysis: The mean AF prevalence, the rates AF ablation per 100, 000 MB, the number of cardiologists per 100, 000 MB, and ablation/cardiologist have shown a steady increase in all regions across years. In all years, the mean AF prevalence was significantly different among regions with the highest prevalence in the Northeast and the lowest in the West (all P<0.001), however, there was no significant difference in the rates of AF ablation per 100, 000 MB (all P≥0.056). There was significant correlation between AF prevalence and ablation only in the Midwest and the West, with 46.4% and 43.4% positive correlation respectively (P≤0.0001). The number of cardiologists performing AF ablation per 100, 000 MB was not significantly different among regions in all years (All P≥0.48), however, ablation/cardiologist was significantly higher in the West and the South compared to the Northeast and the Midwest (All P<0.0001). On the contrary, the ASC has shown steady decrease in all regions. The ASC was significantly different among regions in all year (all P≤0.003) with higher ASC in the Midwest and the Northeast compared to the south and the West. Urban vs rural analysis: Ablation/cardiologist was not significantly different between urban and rural areas in all years (all P≥0.068) except in 2013 when it was significantly higher in urban areas (P=0.004). The ASC was significantly higher in rural areas only in 2015 and 2019 (P=0.037 and P=0.029 respectively) however, there was no significant difference in the rest of the years (P≥0.07). Gender analysis: Ablation/cardiologist was not significantly different between male and female cardiologists in all years (P≥0.056) except in 2017 when the average was significantly higher per male cardiologists (P=0.007). The ASC was not significantly different in all years (P≥0.362). Conclusion: There are variations in AF ablation utilization and reimbursement among MB in the USA according to geographic, urban and rural regions, and the gender of performing cardiologists. Funding Acknowledgement: Type of funding sources: None.